Understanding disabilities in American Indian & Alaska Native communities : toolkit guide. - National Council on Disability (U.S.) (Washington, DC (1331 F St., NW, Ste 850, Washington 20004) : National Council on Disability : For sale by the Supt. of Docs., U.S. G.P.O., 2003)
Shipping list no.: 2003-0255-P. "August 1, 2003." Cover title. Includes bibliographical references. Mode of access: Internet.